2013 IEEE International Geoscience and Remote Sensing Symposium - IGARSS 2013
DOI: 10.1109/igarss.2013.6723835
|View full text |Cite
|
Sign up to set email alerts
|

High resolution geodetic earth observation with TerraSAR-X: Correction schemes and validation

Abstract: Previous studies have shown the unprecedented absolute pixel localization accuracy of the German SAR (Synthetic Aperture Radar) satellites TerraSAR-X and TanDEM-X. Now, by thoroughly correcting all signal path delays and geodynamic effects like tides, loadings and plate movements, range accuracies of about 1 centimeter are demonstrated to be attainable. While Global Navigation Satellite System (GNSS) data provide local correction values for the atmospheric delays, correction values for the geodynamic effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Using the results from CR7, one can say that the biases ofμ a ≈ 2 cm in azimuth andμ r ≈ 32 cm in range were due to residual azimuth and range timing errors. Taking the SM mode into account, these 2D position accuracies are comparable to the results reported by Schubert et al (2010), Eineder et al (2011, Balss et al (2013) and will serve as a benchmark for future SM mode validations.…”
Section: D Absolute Cr Positional Accuracysupporting
confidence: 68%
See 1 more Smart Citation
“…Using the results from CR7, one can say that the biases ofμ a ≈ 2 cm in azimuth andμ r ≈ 32 cm in range were due to residual azimuth and range timing errors. Taking the SM mode into account, these 2D position accuracies are comparable to the results reported by Schubert et al (2010), Eineder et al (2011, Balss et al (2013) and will serve as a benchmark for future SM mode validations.…”
Section: D Absolute Cr Positional Accuracysupporting
confidence: 68%
“…The absolute position accuracy of ENVISAT (Small et al 2004a(Small et al , b, 2007 and Sentinel-1A (Schubert et al 2015) images were computed to be in the order of several decimeters at best both in azimuth and range directions. Recently, for TSX the absolute geolocation accuracy after compensating for atmospheric and tidal effects, was reported to be in the order of a few centimeters in azimuth and range directions (Schubert et al 2010(Schubert et al , 2012Eineder et al 2011;Balss et al 2013). The accuracy of PS heights was indirectly validated by Perissin (2008) (for ERS and ENVISAT) and (for ERS, ENVISAT and TSX), both by making a digital terrain model (DTM) from smoothed PS heights and comparing this with precise elevation data obtained from airborne LiDAR.…”
Section: Introductionmentioning
confidence: 99%
“…In range, the accuracy depends on the atmospheric path delay of the signal as well as on various other error sources (see, e.g., [10,11]). Including corrections for these errors, an absolute position accuracy of below one decimeter in range and azimuth can be achieved for TSX images acquired in a stereo configuration [12].…”
Section: Geo-coding Considerations and Pre-processingmentioning
confidence: 99%
“…The measurement series on hand is based on a CR with very precisely known ground coordinates (better than 5 millimeters) which we installed near the geodetic observatory Wettzell, Germany [3] [4]. Up to now, 52 high resolution Spotlight (HS) datatakes were recorded in two different acquisition geometries.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…Previous studies showed a ranging accuracy at the centimeter level [1][2][3][4]. This accuracy level becomes attainable by a thorough design of all subsystems, including the precise orbit determination [5] [6], and the elimination of several processor approximations in the SAR data processing [4].…”
Section: Introductionmentioning
confidence: 99%